Sosialisasi dan Penyerahan Rancangan Cold Storage sebagai Tempat Penyimpanan Hasil Panen Urban Farming “MOM’S FARM” di Kampung Nagrek - Suprata, Ferdian; Surbakti, Feliks P.S; Tampubolon, Victoria P.L.K (Jurnal Pengabdian Masyarakat Charitas, 2021)
Obstacles found in urban farming include vegetables that are not durable and perishable before being consumed, marketed, or further distributed to the nearest markets or retailers. The activity aimed to inform and share cold storage design to store the harvesting "Mom's Farm" urban farming at Nagrek Village. The design of cold storage is using the Design Thinking (DT) method. DT is a human-centered approach to innovation in the industry 4.0 era. The monitoring and evaluation program results show that several factors can be added as criteria for the design plan of cold storage: considering aspects of electrical energy requirements and limited access to electrical energy consumption in cold storage designs for use in cold storage designs remote areas.